Artificiality and Sustainability in Entrepreneurship Exploring the Unforeseen, and Paving the Way to a Sustainable Future - Adams, Richard; Grichnik, Dietmar; Pundziene, Asta; Volkmann, Christine (FGF Studies in Small Business and Entrepreneurship,, 2023)
This open access edited volume explores the past, present, and future of artificiality and sustainability in entrepreneurship - the unforeseen consequences and ways to advance to a sustainable future. In particular, it connects artificiality, sustainability and entrepreneurship, intertwining artificial with the specific phenomenon of those novel digital technologies that provoke continuous and significant change in our lives and business. Unlike digital entrepreneurship research, which focuses on digital technology development and management, this book covers processes and mechanisms of sustainable adaptability of entrepreneurs, the business logic of start-ups, and the collaborative behaviours under the mass digital transformation, including the prevalence of artificial intelligence. Some of the questions that this book answers are as follows: How has entrepreneurship reacted to such challenges previously? What lessons have been learned and need to be carried forward? How can entrepreneurship and the artefacts of entrepreneurship respond to current challenges? What should be the mindset of the entrepreneur to assure sustainable adaptation? How to embrace and embed the new business logic?